The Influence of Promotion and Socialization of Earthquake Disaster Control as an Improvement of Disaster Mitigation Knowledge of YPAK PTPN III Sei Karang Middle School Students - Susilawati, Susilawati; Chandra Syafira, Azzahra; Intan Farashati, Junaisa; Suci Ramadiah, Putri; Talitha Jasmine, Savina; Ramadani, Selvia; Megarani, Sheila (PROMOTOR, 2025)
This research aims to analyze the influence of promotion and socialization of earthquake disaster control on increasing disaster mitigation knowledge among YPAK PTPN III Sei Karang Middle School students. This research uses a descriptive method with a quantitative approach. A total of 54 students were selected as samples using proportional sampling techniques. Data was collected through pre-test and post-test which were analyzed using the N-gain test to measure increase in knowledge. The research results showed a significant increase in the average student knowledge score, from 7.61 on the pre-test to 9.06 on the post-test (p < 0.05). The N-gain category shows that 44.4% of students experienced a high increase in knowledge. These findings confirm that promotion and outreach using animation media is effective in increasing students' preparedness for earthquake disasters.